2010
DOI: 10.1007/s00702-010-0510-8
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive methylphenidate administration modulates the diurnal behavioral activity pattern of adult female SD rats

Abstract: Diurnal rhythms influence many of the physiological processes that act to maintain homeostasis of the body in response to different environmental changes. Thus, disturbances in diurnal rhythms can lead to various physiological complications. Repeated exposure to psychostimulants may cause long-term effects by disturbing diurnal rhythms. The aim of the present study is to use the open field assay to determine whether repeated exposure to the psychostimulant methylphenidate (MPD) changes diurnal locomotor activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Activity is altered in a dose-dependent manner, with lowto-moderate doses producing activity above baseline for 1-3 h, although high doses (40 mg/kg) lead to a delayed onset of increased locomotor activity while animals first engage in stereotypic behavior (Gaytan et al, 1997). Daily injections for a week alter the amplitude, mean, and acrophase of activity rhythms (Lee et al, 2009(Lee et al, , 2011, although the findings of these studies lacked the temporal resolution for detecting the behavioral phenomena described here. Similarly to other amphetamines, methylphenidate has been shown to restore circadian rhythmicity to animals rendered arrhythmic with SCN lesions (Honma and Honma, 1992), although only when activity levels were double those observed during baseline.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Activity is altered in a dose-dependent manner, with lowto-moderate doses producing activity above baseline for 1-3 h, although high doses (40 mg/kg) lead to a delayed onset of increased locomotor activity while animals first engage in stereotypic behavior (Gaytan et al, 1997). Daily injections for a week alter the amplitude, mean, and acrophase of activity rhythms (Lee et al, 2009(Lee et al, , 2011, although the findings of these studies lacked the temporal resolution for detecting the behavioral phenomena described here. Similarly to other amphetamines, methylphenidate has been shown to restore circadian rhythmicity to animals rendered arrhythmic with SCN lesions (Honma and Honma, 1992), although only when activity levels were double those observed during baseline.…”
Section: Discussionmentioning
confidence: 84%
“…It has long been appreciated that amphetamines, such as methamphetamine, can have a pronounced effect on the rat circadian clock, lengthening period, and disrupting entrainment to lightdark cycles (Honma et al, 1986). A few studies have demonstrated that methylphenidate can alter the distribution of activity over the day in rats (Algahim et al, 2009;Gaytan et al, 1997;Lee et al, 2011), although specific parameters such as phase angle of entrainment and freerunning period could not be assessed in these studies, and the circadian clock located in the suprachiasmatic nucleus (SCN; Antle and Silver, 2005) was not examined. The present study was designed to determine if methylphenidate on its own in healthy animals could alter properties of the circadian clock.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to assume that the change in baseline neuronal activity at ED10 determined how these units will respond to the MPD rechallenge at ED10. It can also be said that the changes in the baseline activity at ED10 indicated that the CN units are expressing expectation to receive the drug and/or expressing withdrawal from the drug following the previously given six daily MPD injections (Algahim et al, 2009; 2010; Lee et al, 2011; Bergheim et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that the physiology of behavior of living organisms from bacteria to human are controlled by a clock that responds to daily environmental clues (Algahim et al 2009; Bergheim et al 2012; Klein et al 1991; Lee et al 2009, 2011, Moore and Lenn 1972). The endogenous clock is characterized by a cycle of approximately 24 h in duration and it responds to internal or external cues to maintain the homeostatic function by regulating biological and physiological processes such as body temperature, blood pressure, sleep-wake cycles, metabolism, and locomotor activity (Chou et al 2003; Shin et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This clock is sensitive also to various pharmacological agents, and drug exposure may alter the amplitude or the phase of the circadian pacemaker (Giorgetti and Zhdanova 2000). Psychostimulants such as methylphenidate were reported to exhibit an effect on the circadian activity pattern of locomotion (Algahim et al 2009, 2010; Antle et al 2012; Lee et al 2009, 2011). These changes in the circadian activity rhythm serves as an experimental marker in animals to correlate with the long-term effect of the drug (Algahim et al 2009, 2010, ; Bergheim et al 2012; Glaser et al 2012; Lee et al 2009, 2011; Norrell et al 2010).…”
Section: Introductionmentioning
confidence: 99%